폭염이 집단 식중독 환자 발생에 미치는 영향 - 연광훈; Kwanghun Yeon; 정대희; Dae Hee Chung (농촌경제, 2024)
최근 연구들은 기후변화가 식중독 발생에 영향을 미치고 있음을 보고하고 있다. 하지만, 대표적인 이상기후인 폭염이 집단 식중독 발생에 미치는 영향에 대한 연구는 아직 부족하다. 이에 본 연구에서는 도구변수를 이용하여 폭염과 집단 식중독 발생의 인과관계를 분석하였다. 분석을 위해 식품의약품안전처에서 제공하는 시·도별 집단 식중독 환자 수 데이터 중 2002년부터 2020년까지의 패널데이터를 이용하였다. 분석 결과, 연간 폭염일수가 1일 증가하면, 연간 집단 식중독 환자 수는 7.4% 증가하며, 연간 약 1,371억 원의 사회·경제적 비용이 발생하는 것으로 나타났다. 이는 폭염에 적응하기 위한 정부의 식품보건정책이 필요함을 시사한다. Recent studies have reported that climate change is affecting the occurrence of food poisoning. However, research on the impact of heat waves, a representative extreme weather event, on the occurrence of mass food poisoning is still lacking. Therefore, to fill the research gap, this study estimates the effects of heat waves on the incidence of mass food poisoning cases using yearly administrative panel data from 2002 through 2020. Using an instrumental variable approach, we find that an extra day of heat waves would increase the incidence of mass food poisoning cases by approximately 7.4%, resulting in social and economic costs of 137.1 billion won per year. It implies that precautionary measures to adapt to heat waves are needed.